Pelatihan Pengembangan Bahan Ajar Interaktif Berbasis Wayground Bagi Guru-Guru di Madrasah Aliyah Galesong Selatan - Syarifuddin Dollah; Haryanto; Vivit Rosmayanti; Citra Prasiska Puspita Tohamba; Hasriani G (Yayasan Habiburrahman Jamalu Bina Ummat, 2026)
The rapid development of digital technology requires teachers to design more interactive and student-centered learning experiences. However, observations conducted at Madrasah Aliyah Galesong Selatan, Takalar Regency, revealed that most teachers still relied on conventional teaching materials and assessment methods, resulting in suboptimal integration of digital technology into the learning process. This condition limits the variety of instructional media that can enhance student engagement and learning motivation. Therefore, this community service program aimed to improve teachers’ competencies in developing interactive teaching materials and assessments using the Wayground platform. The activity was conducted on July 9, 2026, employing lectures, demonstrations, hands-on practice, discussions, and mentoring as its primary methods. The target participants were 16 teachers from various subject areas at Madrasah Aliyah Galesong Selatan. The program began with presentations on digital learning, followed by demonstrations of Wayground features, practical sessions on creating quizzes and interactive learning activities, and mentoring in the development of instructional products. The results indicated that participants successfully understood how to use Wayground and were able to independently develop various forms of interactive assessments and learning activities. Furthermore, participants demonstrated high enthusiasm throughout the training and reported that Wayground was easy to use and had strong potential to enhance student participation in learning activities. Overall, the program successfully improved teachers’ digital competencies and supported the implementation of more innovative, interactive, and 21st-century-oriented learning practices.